2018
DOI: 10.1177/1468797618771692
|View full text |Cite
|
Sign up to set email alerts
|

Transformations in destination texture: Curry and Bollywood romance in the Swiss Alps

Abstract: This article takes heterogeographical approaches to understand Bollywood-induced destination transformations in Switzerland. Positioned within the theoretical field of mediatized mobility, the study contextualizes Bollywood-induced tourism in Europe the concept of texture. Textural analysis (based on Lefebvre's trialectics of space) combines the analysis of material performances and communicative representations converging in the production/consumption of tourism spaces. The article contributes threefold. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Richards (2018), identified the following well-developed subsectors of cultural tourism: cultural heritage tourism, film-induced tourism, and literary tourism. These three themes also emerged within our article search (Barber, 2018;Domínguez-Quintero, González-Rodríguez, & Paddison, 2018;Gyimóthy, 2018;Io, 2018;Vinodan & Meera, 2018, Yu & Xu, 2018) however, sometimes the above-mentioned terms were used interchangeably with the term 'cultural tourism' and not as a subgroup. For example, Yu and Xu (2018, p. 292) examine 'the moral aspect of literature and literary/cultural tourism'; in this case, literary tourism is equated with cultural tourism.…”
Section: Subfields Of Cultural Tourism?mentioning
confidence: 82%
“…Richards (2018), identified the following well-developed subsectors of cultural tourism: cultural heritage tourism, film-induced tourism, and literary tourism. These three themes also emerged within our article search (Barber, 2018;Domínguez-Quintero, González-Rodríguez, & Paddison, 2018;Gyimóthy, 2018;Io, 2018;Vinodan & Meera, 2018, Yu & Xu, 2018) however, sometimes the above-mentioned terms were used interchangeably with the term 'cultural tourism' and not as a subgroup. For example, Yu and Xu (2018, p. 292) examine 'the moral aspect of literature and literary/cultural tourism'; in this case, literary tourism is equated with cultural tourism.…”
Section: Subfields Of Cultural Tourism?mentioning
confidence: 82%
“…Richards (2018), identified the following well-developed subsectors of cultural tourism: cultural heritage tourism, film-induced tourism, and literary tourism. These three themes also emerged within our article search (Barber, 2018;Domínguez-Quintero, González-Rodríguez, & Paddison, 2018;Gyimóthy, 2018;Io, 2018;Vinodan & Meera, 2018, Yu & Xu, 2018) however, sometimes the above-mentioned terms were used interchangeably with the term 'cultural tourism' and not as a subgroup. For example, Yu and Xu (2018, p. 292) examine 'the moral aspect of literature and literary/cultural tourism'; in this case, literary tourism is equated with cultural tourism.…”
Section: Subfields Of Cultural Tourism?mentioning
confidence: 85%
“…Moreover, as tourism becomes the dominant economic activity in a destination, it begins to transform the hospitality characteristics of place in terms of the food, drink and entertainment services catering for visitors and locals. For example, Gyimóthy’s (2018) work showed that ‘local’ foods were supplemented by what residents perceived to be ‘foreign’ foods, which were preferred by the tourists who visited the destination. Arguably, the presence of familiar foodstuffs, drinking practices or entertainment venues (e.g.…”
Section: Hospitality and The Transformation Of Place (Experiences)mentioning
confidence: 99%